Introduction to superconductivity - Tinkham, Michael; Tinkham, Michael (New Delhi, Medtech, 2017)
The elementary properties of superconductors have consistently attracted researchers from various domains to harness their capabilities in solving plethora of challenges of modern technology. The present state-of-art has emphasized on the rich array of phenomena and represented in a simplest possible way. The use of thermal green functions has been annulled inspite of their fashionability and undeniable power in the hands of skilled theorist. The power of phenomenological theory has given detailed insight and microscopic theory is narrowly directed to the task of computing the coefficients in phenomenological equations. The fact that readers of this book belong to a broad spectrum of academic levels and professional scales. In this edition we made enormous efforts to make the content of this book as pleasant as possible for all of them. Researchers may use the book as a balanced literature of past and recent work in the field for developing new theoretical models, practical applications. Researchers and academicians in universities may use it to extend their teaching material whereas the students may use it for quick understanding of concepts and theoretical models about superconductivity. Special attention has given to keep the text simple and easy-to-understand but at the same time comprehensive and detailed. We aim to serve a wide range of readers groups with the intention of contributing towards technological advancement in the field of superconductivity. Introduction to Superconductivity tends to establish the journey from initial conceptualization of idea of superconductivity and major breakthroughs in the field to modern ongoing researches in plethora of domains towards building an advanced future. The book starts right from the origins of superconductivity phenomenon and goes on to relate different aspects in wide range of its applications.
References 281-283p.; Indexes 287-291p.; Subject index 293-296p.
Keywords: BCS Theory; Gluctuation effects; Magnetics properties; Physics